Interleukin-4 protects from chemotherapy-induced peripheral neuropathy in mice modal via the stimulation of IL-4/STAT6 signaling - Shi,Qingbin (2018)
Abstract Purpose: To investigate the possible role of IL-4 signaling pathway in vincristine-induced peripheral neuropathy. Methods: The mouse model of vincristine-induced peripheral neuropathy and interleukin (IL)-4 knockout mice were utilized to investigate the possible role of IL-4 signaling pathway in vincristine-induced peripheral neuropathy. Vincristine induced increased sensitivity to mechanical stimulation was measured by von Frey hair test 7 and 14 days after intraperitoneal administration of 0.1 mg/kg vincristine in mice. Relative expression levels of cytokines were detected by quantitative real-time PCR. STAT6 expression following vincristine treatment was assessed with western blotting. Results: We discovered that IL-4/STAT6 signaling was down-regulated in vincristine-treated mice. Deletion of IL-4 in mice increased the sensitivity to mechanical allodynia. IL-4 knockout mice also produced more pro-inflammatory cytokines, including IL-1β and TNF-α. Notably, co-administration of exogenous recombination IL-4 significantly prevented vincristine-induced mechanical allodynia. Conclusion: Anti-inflammatory cytokine IL-4 protects rodent model from vincristine-induced peripheral neuropathy via the stimulation of IL-4/STAT6 signaling and inhibition of the pro-inflammatory cytokines.